'High‐co‐occurrence genera': weak but consistent relationships with global richness, niche partitioning, hybridization and decline. Issue 1 (7th October 2015) - Prinzing, Andreas; Powrie, Leslie W.; Hennekens, Stephan M.; Bartish, Igor V.; Ozinga, Wim A.
Abstract: Aim: Many biologists explain the global richness of lineages and local co‐occurrence of lineage members by distinct processes: speciation/extinction versus ecological interactions. Moreover, allopatric distribution, rarity and local competition limit local co‐occurrence of species even within species‐rich lineages. However, whether and why the global richness of lineages relates to local co‐occurrence of lineage members has not been tested. We study angiosperms, and hypothesize that in globally species‐rich genera species frequently encounter congeners locally, reflecting (1) random sampling of species pools into local communities and (2) processes of global species production and local survival such as hybridization, niche filling and a reduced risk of extinction. Location: Netherlands, South Africa, world‐wide. Methods: Analysing more than 350, 000 plots we quantify per species the observed number of co‐occurring congeners as well as the null expectation based on random sampling from species pools. From the literature we quantify the global species richness of genera, and abiotic niche positions and breadths, hybrid status and regional species declines. Results: In some genera species frequently encounter congeners locally, while in others congeners are rarely encountered. This is independent of the total number of species encountered, and is consistent between the Netherlands and South Africa. 'High‐co‐occurrence genera' are particularly species rich across the globe, consistently so in most families and even after controlling for niche positions, age and regional richness of genera. Species in high‐co‐occurrence genera tend to occupy niches that are large and close to congeners' niches. These species are more often hybrids and rarely decline. Relationships explain little variance (< 10%) but are stronger than expected from random sampling of species rich pools. Main conclusions: Local co‐occurrence and global species richness are largely independent, but not entirely so, reflecting random sampling of pools into communities, niche partitioning, hybridization and the reduced risk of regional extinction in high‐co‐occurrence genera. Increased extinction risk in low‐co‐occurrence genera implies a proportionately high loss of lineages and their evolutionary heritage from local communities.